The Correlation Between Students’ Vocabulary Mastery and Their Reading Comprehension of Narrative Text at Eighth Grade - Jeni Jeni; Anisa Septia Megawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This research was about the correlation between students’ vocabulary mastery and their reading comprehension of narrative text. The purpose of this research is to find out is there any significant correlation between students’ vocabulary mastery and their reading comprehension of narrative text at eighth grade in SMPN 2 Simpenan? And how is students’ vocabulary mastery into reading comprehension of narrative text at eighth grade in SMPN 2 Simpenan? This type of research is correlation research with quantitative methods. The sample in this research was class VIII (a) with 30 students. In analyzing the data, researchers used Pearson Correlation to determine the relationship between students’ vocabulary mastery and students’ reading comprehension of narrative text. The research findings showed that the sig value (2-tailed) of 0,000 < 0.05, then between students' vocabulary mastery and students' reading comprehension of narrative text are correlated and the Pearson Correlation value of the two variables is 0.792. In conclusion, r count of 0.792 > 0.05 is obtained, which means H(a) is accepted and H(o) is rejected. So the hypothesis states that there is a correlation between students’ vocabulary mastery and their reading comprehension of narrative text at eighth grade in SMPN 2 Simpenan. Here are some suggestions, English teachers should support students with various methods or strategies that can increase students' vocabulary mastery to improve their reading comprehension, and students should practice a lot to master vocabulary, because vocabulary is one of the very important components in the teaching and learning process.